The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.joca.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of strontium or NBD peptide ameliorates early stage cartilage degradation of mouse mandibular condyles

Abstract: SUMMARY Objective To determine whether mandibular condylar cartilage degradation induced by experimentally abnormal occlusion could be ameliorated via systemic administration of strontium or NBD peptide. Methods Six-week-old female C57BL/6J mice were used. From the seventh day after mock operation or unilateral anterior crossbite (UAC) treatment, the control and UAC mice were further respectively pharmacologically treated for 2 weeks or 4 weeks of saline (CON + Saline and UAC + Saline groups), SrCl2 (CON + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The cellular zonal boundary of mouse TMJ cartilage is not as morphologically typical as that in rats. However, our previous study revealed that the TMJs of rats and mice respond to UAC stimulation in a very similar manner considering the cartilage and subchondral bone phenotypes and chondrocyte terminal differentiation [23,24,25,26,27,28,29,30,31,32]. Briefly, the UAC-induced TMJ OA-like changes predominantly affected the deep zone cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular zonal boundary of mouse TMJ cartilage is not as morphologically typical as that in rats. However, our previous study revealed that the TMJs of rats and mice respond to UAC stimulation in a very similar manner considering the cartilage and subchondral bone phenotypes and chondrocyte terminal differentiation [23,24,25,26,27,28,29,30,31,32]. Briefly, the UAC-induced TMJ OA-like changes predominantly affected the deep zone cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that TMJ OA induced by interrupted dental occlusion undergoes different pathological processes as compared to knee OA [22]. Recently, we created a rodent model by exposing the animals to an aberrant biomechanical dental occlusion, termed unilateral anterior crossbite (UAC), which simulated clinical abnormal dental occlusion and caused a series of TMJ OA-like changes without surgical damage [23,24,25,26,27,28,29,30]. Our latest research suggested that one of the typical changes in chondrocytes in UAC rat TMJ OA cartilage was abnormal differentiation, starting from the injured deep zone and then expanding to the superficial zone [26].…”
Section: Introductionmentioning
confidence: 99%
“…P65 is a critical active subunit in NF-jB signalling in multiple cell types [36]. Liu found that the percentages of phosphorylated p65 were significantly increased in TMJ-OA mice [37]. Chen showed that p65-specific siRNA could suppress the induction of IL-1b and delay the cartilage degradation in OA model in early-phase [9].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that fluid flow shear stress (FFSS) induced TMJ chondrocyte death in vitro [5][6][7]. We also developed an in vivo abnormal dental occlusion termed unilateral anterior cross (UAC) model and demonstrated that it induced chondrocyte death and OA-like lesions in TMJ cartilage in rats and mice [7][8][9][10][11]. These in vitro and in vivo models are useful tools to facilitate the investigation of molecular mechanisms through which abnormal biomechanical forces induce chondrocyte death and the onset of TMJ OA.…”
Section: Introductionmentioning
confidence: 99%